2006
DOI: 10.1002/tal.297
|View full text |Cite
|
Sign up to set email alerts
|

Predictive instantaneous optimal control of inelastic structures based on ground velocity

Abstract: One of the challenges confronting structural engineers in structural control is to find more efficient control algorithms to ensure better and more reliable control results to protect structures against the damaging effects of destructive environmental forces. In this paper, a simple control algorithm, namely the Predictive Instantaneous Optimal Control (PIOC) algorithm, is proposed by introducing a new state space form. Different from the classical ground acceleration-based control algorithms, this new contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Incorporating geometric nonlinearity using stability functions approach in FAM allows better performance in predicting large deformation accurately than other linearized methods (e.g., P-Δ and geometric stiffness approaches) (see Wong and Wong and Speicher 16,17 ). In literature, FAM algorithm has been used in various research areas, namely, reinforced concrete members/structures, 10,18,19 steel frame structures, [20][21][22] and energy-based analysis. [23][24][25] F I G U R E 1 Ten-storey moment-resisting steel frame Basic concept of FAM is briefly explained herein (see Figure 2), where f S (t) is the lateral force excited on a single-degree-of-freedom (SDOF) system, and x(t) and m S (t) are the lateral deformation and support moment, respectively (see Figure 2a).…”
Section: Force Analogy Methodsmentioning
confidence: 99%
“…Incorporating geometric nonlinearity using stability functions approach in FAM allows better performance in predicting large deformation accurately than other linearized methods (e.g., P-Δ and geometric stiffness approaches) (see Wong and Wong and Speicher 16,17 ). In literature, FAM algorithm has been used in various research areas, namely, reinforced concrete members/structures, 10,18,19 steel frame structures, [20][21][22] and energy-based analysis. [23][24][25] F I G U R E 1 Ten-storey moment-resisting steel frame Basic concept of FAM is briefly explained herein (see Figure 2), where f S (t) is the lateral force excited on a single-degree-of-freedom (SDOF) system, and x(t) and m S (t) are the lateral deformation and support moment, respectively (see Figure 2a).…”
Section: Force Analogy Methodsmentioning
confidence: 99%
“…In a case study, the computational time has been found to reduce by 70% using FAM than that of TMSD (SAP2000) [32]. In the literature, FAM has been used for the structural analysis of reinforced concrete members/structures [33][34][35], structural steel frames [36][37][38][39], energy-based seismic analysis [40][41][42].…”
Section: Basic Concept Of Fammentioning
confidence: 99%
“…, Aldemir et al . , Pang and Wong , and Ho and Ma . Recently, frequency domain techniques were introduced for optimality problems and proved to be an effective approach in the design of the controllers for seismic‐excited and wind‐excited buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Acknowledging this problem, Yang et al [18] developed an optimal algorithm in which at any time instant t, the earthquake record, which is available up to time t through measurement, is used. This new instantaneous optimal control algorithm is further improved by Yang et al [19,20], Aldemir et al [21,22], Pang and Wong [23], and Ho and Ma [24]. Recently, frequency domain techniques were introduced for optimality problems and proved to be an effective approach in the design of the controllers for seismic-excited and wind-excited buildings.…”
Section: Introductionmentioning
confidence: 99%